Contact laws between nanoparticles: the elasticity of a nanopowder. Issue 4 (12th January 2018) - Girard, Adrien; Ramade, Julien; Margueritat, Jérémie; Machon, Denis; Saviot, Lucien; Demoisson, Frédéric; Mermet, Alain
Abstract : Studies of the mechanical contact between nanometer-scale particles provide fundamental insights into the mechanical properties of materials and the validity of contact laws at the nanoscale which are still under debate for contact surfaces approaching atomic dimensions. Abstract : Studies of the mechanical contact between nanometer-scale particles provide fundamental insights into the mechanical properties of materials and the validity of contact laws at the nanoscale which are still under debate for contact surfaces approaching atomic dimensions. Using in situ Brillouin light scattering under high pressure, we show that effective medium theories successfully predict the macroscopic sound velocities in nanopowders if one takes into account the cementation of the contacts Our measurements suggest the relevance of the continuum approach and effective medium theories to describe the contact between nanoparticles of diameters as small as 4 nm, i.e. with radii of contact of a few angstroms. In particular, we demonstrate that the mechanical properties of nanopowders strongly depend on the surface state of the nanoparticles. The presence of molecular adsorbates modifies significantly the contact laws.